Diel vertical migration of copepods in a Brazilian lake: a mechanism for decreasing risk of Chaoborus predation? - A.,Perticarrari (2004)
A comparison between two studies on diel vertical migration of two cyclopoid copepod species, in Lake Monte Alegre, undertaken in 1985/86 and 1999, revealed a change in their migratory behavior. In summer, during a period of marked stratification with low dissolved oxygen near the bottom, the organisms avoided the deepest layers, and migration was nocturnal or undetectable, in both periods. On other occasions, with partial or total circulation in the lake, a weak twilight migration of copepodites and adults in 1985 was replaced by the reverse in 1999. Differences were found among stages, with the weakest or undetectable migration being observed for nauplii. The migratory pattern change for copepodites and adults might be related with a recent predation pressure increase by Chaoborus larvae on copepods, after the virtual disappearance of their main cladoceran prey.